Cyclic AMP mediates heat stress response by the control of redox homeostasis and ubiquitin‐proteasome system. (16th September 2020) - Paradiso, Annalisa; Domingo, Guido; Blanco, Emanuela; Buscaglia, Alessio; Fortunato, Stefania; Marsoni, Milena; Scarcia, Pasquale; Caretto, Sofia; Vannini, Candida; de Pinto, Maria Concetta
Abstract: Heat stress (HS), causing impairment in several physiological processes, is one of the most damaging environmental cues for plants. To counteract the harmful effects of high temperatures, plants activate complex signalling networks, indicated as HS response (HSR). Expression of heat shock proteins (HSPs) and adjustment of redox homeostasis are crucial events of HSR, required for thermotolerance. By pharmacological approaches, the involvement of cAMP in triggering plant HSR has been recently proposed. In this study, to investigate the role of cAMP in HSR signalling, tobacco BY‐2 cells overexpressing the 'cAMP‐sponge', a genetic tool that reduces intracellular cAMP levels, have been used. in vivo cAMP dampening increased HS susceptibility in a HSPs‐independent way. The failure in cAMP elevation during HS caused a high accumulation of reactive oxygen species, due to increased levels of respiratory burst oxidase homolog D, decreased activities of catalase and ascorbate peroxidase, as well as down‐accumulation of proteins involved in the control of redox homeostasis. In addition, cAMP deficiency impaired proteasome activity and prevented the accumulation of many proteins of ubiquitin‐proteasome system (UPS). By a large‐scale proteomic approach together with in silico analyses, these UPS proteins were identified in a specific cAMP‐dependent network of HSR. Abstract : In vivo cAMP dampening, obtained through the expression of 'cAMP‐sponge', increases heat stress (HS) susceptibility of tobacco BY‐2 cells, without affecting the expression of heat shock proteins. cAMP plays a key role in HS response, controlling redox homeostasis and ubiquitin‐proteasome system.